Assisting Students Learning At Home: Parents’ Role - Suparjan, Suparjan; Wibawa, Lutfi; Fauziah, Puji Yanti; Ismiyani, Nining (Journal of Education Research, 2024)
Parents play a pivotal role in their children's learning success, especially during home-based learning activities. As the primary figures in their children's lives, parents take on the role of co-learners, contributing significantly to the learning journey. The aim of this study is to identify the involvement of parents in supporting the learning of their children or elementary school student while at home. The research utilizes a descriptive method within a qualitative research design. The subjects of this study consist of five parents either fathers or mothers of elementary school students. Data collection is conducted through semi-structured interviews. The data analysis employs an interactive qualitative data analysis approach, which includes data reduction, data display, and conclusion drawing or verification. The research findings reveal that parents actively engage in tutoring, motivating, facilitating and assessing their children's learning activities. In conclusion, tutor, motivator, facilitator and assessor are the roles that reflects the diverse ways parents contribute to their children's success in learning settings at home.